A computational analysis of locomotor anatomy and body mass evolution in Allosauroidea (Dinosauria: Theropoda). Issue 3 (8th February 2012) - Bates, Karl T.; Benson, Roger B. J.; Falkingham, Peter L.
Abstract : We investigate whether musculoskeletal anatomy and three-dimensional (3-D) body proportions were modified during the evolution of large (>6000 kg) body size in Allosauroidea (Dinosauria: Theropoda). Three adaptations for maintaining locomotor performance at large body size, related to muscle leverage, mass, and body proportions, are tested and all are unsupported in this analysis. Predictions from 3-D musculoskeletal models of medium-sized ( Allosaurus ) and large-bodied ( Acrocanthosaurus ) allosauroids suggest that muscle leverage scaled close to isometry, well below the positive allometry required to compensate for declining muscle cross-sectional area with increasing body size. Regression analyses on a larger allosauroid data set finds slight positive allometry in the moment arms of major hip extensors, but isometry is included within confidence limits. Contrary to other recent studies of large-bodied theropod clades, we found no compelling evidence for significant positive allometry in muscle mass between exemplar medium- and large-bodied allosauroids. Indeed, despite the uncertainty in quantitative soft tissue reconstruction, we find strong evidence for negative allometry in the caudofemoralis longus muscle, the single largest hip extensor in non-avian theropods. Finally, we found significant inter-study variability in center-of-mass predictions for allosauroids, but overall observe that consistently proportioned soft tissue reconstructions produced similar predictions across the group, providing no support for a caudal shift in the center of mass in larger taxa that might otherwise reduce demands on hip extensor muscles during stance. Our data set provides further quantitative support to studies that argue for a significant decline in locomotor performance with increasing body size in non-avian theropods. However, although key pelvic limb synapomorphies of derived allosauroids (e.g., dorsomedially inclined femoral head) evolved at intermediate body sizes, they may nonetheless have improved mass support.